Writing culture and oral communication in ancient Christianity: the homilies as instruments of power - Silva, Gilvan Ventura da (Romanitas - Revista de Estudos Grecolatinos, 2017)
A creed risen in a Jewish environment, Christianity was organized in terms of a textual community that attributed to the written culture a major role in the preservation and transmission of the precepts announced by Jesus. Owe to it, the evangelion, kept initially by means of the oral tradition, was finally written, according to a non-stop movement of “bureaucratization” of the Christian belief. Indeed, the holy message bore by the Christian texts, coupled with the emergence of a complex ecclesiastic hierarchy, was decisive for the consolidation of the Church. Therefore, Christianity represents a remarkable example of a steady association between power and writing. Nevertheless, we should recall that the Christian emphasis on writing, in Antiquity, did not imply the abandon of the oral tradition, since the homilies, a flourishing literary genre in the fourth and fifth centuries A.D., experienced a noticeable development under the influence of the classical rhetoric.